Color distortion and edge feature for perceptual quality assessment - ZEGGARI, Ahmed; AHMED SEGHIR, Zianou; HEMAM, Mounir; Hachouf, Fella; DJEZZAR, Meriem (Informatica, 2022)
The color distortion effect has an important impact on the perceived quality, which is ignored in previous related works. Unified with the color distortion outcome and edge similarity, a new full-reference image quality assessment was proposed named the gradient similarity-based distorted pixel and deformed color measure (GDCM). The components RGB of the color image are converted into image coded in YIQ color space. Then, Ruderman operators and the gradient images are calculated from the Y component. I and Q elements are used to identify the color distortion. Finally, the previous results are combined to compute the ultimate measure. Experimental results on databases illustrate that the GDCM performs very well.